Scandalous reunion - Bennett, Jules (Harlequin desire, 2020)
"Back in town after sixteen years, Tennessee attorney Maty Taylor has to persuade her ex-lover--billionaire bourbon maker Sam Hawkins--to sell his priceless distillery. The stakes are high, since Maty's being blackmailed to persuade him. Sensing trouble, Sam refuses the offer, even as renewed desire surges between them. But will his hidden agenda cost him a second chance with Maty?" --